Year-round itinerary of a GPS-tracked Brent Goose Branta b. bernicla that visited the Bassin d’Arcachon, France - Dokter, Adriaan M.; Ebbinge, Barwolt S. (Wildfowl, 2013)
The year-round itinerary for a Dark-bellied Brent Goose Branta b. bernicla is described for a bird fitted with a GPS tracking device at Terschelling Island, the Netherlands, in spring 2012. Spring migration commenced when the bird left the Dutch Wadden Sea on 27 May and continued until it reached the Taimyr Peninsula in arctic Russia on 8 June. During the summer months it moved along the coast of the Taimyr Peninsula, prior to moulting on Taimyr Island to the north of the peninsula in July. During autumn migration it frequented eelgrass Zostera sp. beds around Langeness Island in Schleswig-Holstein, Germany and then proceeded to the Bassin d’Arcachon in France, another famous eelgrass area, where it remained from 18 October 2012–12 January 2013 before returning to feed on grassland polders on Terschelling Island in January 2013. The timing of the location data showed that the bird flew large distances in short periods of time during migration. Over the year it covered c. 4,600 km during local movements and c. 15,000 km on migration. The results form part of a larger study investigating the importance of non-breeding habitats (particularly eelgrass vegetation) for the species.